Media literacy in formal education- Media literacy and critical analysis of different types of historical sources - Kobiashvili, Eka ("Intercultural Dialogues" Transactions, 2023)
In the era of global information, a great role is played by the development of the culture of media literacy. Evaluating the product independently and critically as well as sorting and filtering the flow of information is possible only with the help of media literacy. Students should ask questions, that will help them critically study the issue. They know how to find the information they need on the web but they don't always know how to filter the information. It is in this process that you will help them develop media literacy skills. How can we help our students? Let's teach them to ask questions. They often ask the question - why? Media literacy should be established in both informal and formal education (should include all academic disciplines), which will help our students to be more critical and media literate. My report is about using media literacy questions to discuss one historical issue - the Vietnam War, how to evaluate different types of historical sources using media literacy questions. This is one of the modern methods that can be used by the teacher at the lesson for critical discussion of the issue and correct assessment.